ENCOURAGING ENTREPRENEURSHIP IS THE WAY TO REDUCE UNEMPLOYMENT -WITH SPECIAL REFERENCE TO MANUFACTURING UNITS IN GUINDY - V, Monisha.; V., Andal (International Journal of Psychosocial Rehabilitation, 2020)
This study indicates the culture of entrepreneurship and observes the unemployment crisis. The relationship between entrepreneurship and unemployment and what the entrepreneur tries to get from new startups of business and an unemployed person after startups. This study examined the possibilities of whether the unemployment crisis is decreased through entrepreneurship. For this purpose, the study limits itself to 120 targeted responses from manufacturing units in Guindy, and this study suits a descriptive survey design. Following this, some tools like ANOVA, t-tests, and percentage analysis are used to test the hypothesis and finally result in entrepreneurship being the main strategy to reduce unemployment , where finance and changes in government policies are the two important factors that play a troublesome role in the new startups part.